The Practice of Children’s Rights Protection in Africa - Garayová, Lilla (Children’s Rights in Regional Human Rights Systems, 2024)
This chapter examines the issue of children’s rights protection in Africa, focusing on the challenges hindering the effective implementation of these rights and the progress that has been made. It delves into the roles of key institutions such as the African Commission on Human and Peoples’ Rights, the African Committee of Experts on the Rights and Welfare of the Child, and the African Court of Human and Peoples’ Rights, emphasising their efforts to promote and safeguard children’s rights across the continent. This chapter also highlights the ongoing issues of poverty, armed conflict, and harmful cultural practices that disproportionately affect African children. Importantly, it further shows that these challenges have not completely deterred African nations from taking significant strides towards legal reforms and educational advancements aimed at enhancing the protection and realisation of children’s rights. This chapter advocates a deeper understanding and integration of African cultural values into the discourse on children’s rights. Keywords: Children’s Rights, African Commission on Human and Peoples’ Rights, African Children’s Charter, Human Rights Protection, Child Advocacy, Legal Reform